Islamic family law : demystifying Shari'ah in the protection of children ' rights volume iii - Kamaruddin, Zaleha (s.n, 2012)
Realizing the for fresh outlooks on a number of doctrinal as well as juristic issues regarding the subject of the protection of children's right, this collection of six essays cover a wide spectrum of matters from the rights of a child to life; religion and association; protection of privacy, family, home, honour and dignity to the rights to education, health care, parental care and social security, the right to protection from physical or mental injury, sexual exploitation and abuse, and from neglect and maltreatment. This book explores these critical issues concerning the protection of children's rights which varies according to areas of the law. This book hosts discussion and analyses based on dats collected through a non-intervention method such as library and online research